The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1291/hypres.31.833
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Hypertension and Arterial Elasticity Characteristics in Healthy Young People

Abstract: Family history of hypertension is a primary predictor of high blood pressure (BP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
1
13
0
1
Order By: Relevance
“…The presence of familial metabolic risk factors is known to predict future cardiovascular events in the offspring. 17,18 However, the intrafamilial aggregation of flowmediated vascular dilation has been shown to be significantly higher in father-offsprings than in mother-offsprings. 16 It is known that high-density lipoprotein-cholesterol levels are a determinant of flow-mediated vascular dilation and are associated with genetic variation in the Y chromosome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of familial metabolic risk factors is known to predict future cardiovascular events in the offspring. 17,18 However, the intrafamilial aggregation of flowmediated vascular dilation has been shown to be significantly higher in father-offsprings than in mother-offsprings. 16 It is known that high-density lipoprotein-cholesterol levels are a determinant of flow-mediated vascular dilation and are associated with genetic variation in the Y chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…16 Indeed, the presence of familial metabolic risk factors is known to predict future cardiovascular events in the offspring. 17,18 It is well known that increased cIMT is an independent risk marker for coronary artery disease and stroke, becoming a sensitive subclinical atherosclerosis marker. 19 Given the associations found in adults and in children with iron overload, we hypothesized that serum ferritin levels could be linked to cIMT in children from the general population.…”
mentioning
confidence: 99%
“…Studies comparing carotid intima-media thickness and aortic stiffness in normotensive children of hypertensive parents with children of normotensive parents revealed that carotid intimamedia thickness increased in both adolescents and young adults. [24][25][26][27][28][29][30][41][42][43][44] Evelein et al 27 found that carotid intima-media thickness was higher in children older than 5 years of age compared to controls, an increase that may be observed as early as at the age of 5. Xiang et al 26 evaluated 206 children aged 16 years and older from 69 hypertensive families and demonstrated that carotid intima-media thickness was increased, an increase that correlated with both age and Arterial features in children of hypertensive parents A Yildirim et al genetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is the most important risk factor for SVD [49] . In patients with a family history of hypertension, the vasculature has already been damaged be- and SBP or DBP [50] .…”
Section: Other Risk Factors Asymmetric Dimethylargininementioning
confidence: 99%